Assessment of global guidelines for preventive chemotherapy against schistosomiasis and soil-transmitted helminthiasis: a cost-effectiveness modelling study. Issue 9 (September 2016) - Lo, Nathan C; Lai, Ying-Si; Karagiannis-Voules, Dimitrios-Alexios; Bogoch, Isaac I; Coulibaly, Jean T; Bendavid, Eran; Utzinger, Jürg; Vounatsou, Penelope; Andrews, Jason R
Summary: Background: WHO guidelines recommend annual treatment for schistosomiasis or soil-transmitted helminthiasis when prevalence in school-aged children is at or above a threshold of 50% and 20%, respectively. Separate treatment guidelines are used for these two helminthiases, and integrated community-wide treatment is not recommended. We assessed the cost-effectiveness of changing prevalence thresholds and treatment guidelines under an integrated delivery framework. Methods: We developed a dynamic, age-structured transmission and cost-effectiveness model that simulates integrated preventive chemotherapy programmes against schistosomiasis and soil-transmitted helminthiasis. We assessed a 5-year treatment programme with praziquantel (40 mg/kg per treatment) against schistosomiasis and albendazole (400 mg per treatment) against soil-transmitted helminthiasis at 75% coverage. We defined strategies as highly cost-effective if the incremental cost-effectiveness ratio was less than the World Bank classification for a low-income country (gross domestic product of US$1045 per capita). We calculated the prevalence thresholds for cost-effective preventive chemotherapy of various strategies, and estimated treatment needs for sub-Saharan Africa. Findings: Annual preventive chemotherapy against schistosomiasis was highly cost-effective in treatment of school-aged children at a prevalence threshold of 5% (95% uncertainty interval [UI] 1·7–5·2; current guidelines recommend treatment at 50% prevalence) and for community-wide treatment at a prevalence of 15% (7·3–18·5; current recommendation is unclear, some community treatment recommended at 50% prevalence). Annual preventive chemotherapy against soil-transmitted helminthiasis was highly cost-effective in treatment of school-aged children at a prevalence of 20% (95% UI 5·4–30·5; current guidelines recommend treatment at 20% prevalence) and the entire community at 60% (35·3–85·1; no guidelines available). When both helminthiases were co-endemic, prevalence thresholds using integrated delivery were lower. Using this revised treatment framework, we estimated that treatment needs would be six times higher than WHO guidelines for praziquantel and two times higher for albendazole. An additional 21·3% (95% Bayesian credible interval 20·4–22·2) of the population changed from receiving non-integrated treatment under WHO guidelines to integrated treatment (both praziquantel and albendazole). Country-specific economic differences resulted in heterogeneity around these prevalence thresholds. Interpretation: Annual preventive chemotherapy programmes against schistosomiasis and soil-transmitted helminthiasis are likely to be highly cost-effective at prevalences lower than WHO recommendations. These findings support substantial treatment scale-up, community-wide coverage, integrated treatment in co-endemic settings that yield substantial cost synergies, and country-specific treatment guidelines. Funding: Doris Duke Charitable Foundation, Mount Sinai Hospital-University Health Network AMO Innovation Fund, and Stanford University Medical Scholars Programme.